Effectiveness of internet-based cognitive behavioral therapy for suicide: a systematic review and meta-analysis of RCTs. Issue 10 (26th November 2022) - Yu, Ting; Hu, Deying; Teng, Fen; Mao, Jing; Xu, Ke; Han, Yanhong; Liu, Yilan; Wu, Minge
ABSTRACT: Suicidal individuals rarely seek help and receive professional psychological intervention on their initiative. Internet-based cognitive behavioral therapy(iCBT) can increase availability and reduce stigma compared to face-to-face interventions for suicide.However, conclusions about the effectiveness of iCBT on suicide are controversial. The review aimed to determine the effectiveness of iCBT on reducing suicidal ideation (primary outcomes) and other outcomes related to suicide like suicide attempts(secondary outcomes). PubMed, the Cochrane Library, EMBASEwere searched up to March 2020 for RCTs of iCBT which aimed to reduce suicide.The potential bias was assessed by the Cochrane risk of bias tool. Data analyses wereperformed by RevMan5.3.Four studies meeting the eligibility criteria were included which reported data on a total of 1225 participants. We found iCBT was associated with reducing an individual's suicidal ideation, and first indications suggest that the treatment effect might be even more pronounced in the short term and in adults.Additionally, there was insufficient evidence to prove its effectiveness in reducing suicide attempts and suicide death.Overall, iCBT can overcome the disadvantages of traditional interventions and show promise on suicidal ideation. While ensuring safety and ethics, further studies are warranted, focusing on suicide specific behavior like suicide attempts.